2005
DOI: 10.1073/pnas.0509779103
|View full text |Cite
|
Sign up to set email alerts
|

Inositols prevent and reverse endothelial dysfunction in diabetic rat and rabbit vasculature metabolically and by scavenging superoxide

Abstract: Endothelial dysfunction (ED) is an early feature of cardiovascular risk and diabetes. Hyperglycemia and hyperlipidemia are causative factors. Excessive endothelial mitochondrial superoxide (ROS) production with hyperglycemia and hyperlipidemia is a key mechanism. Inositol components of an insulin inositol glycan mediator, D-chiro-inositol (DCI) and 3-O-methyl DCI (pinitol), decrease hyperglycemia and hyperlipidemia. We tested whether these, myoinositol and dibutyryl DCI (db-DCI), would prevent or reverse ED in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 73 publications
(82 reference statements)
5
78
1
1
Order By: Relevance
“…These findings are in agreement with previous work that has shown that the metabolic activity of endothelial cells within a diabetic vasculature is reduced and that this can be reversed through the application of pharmacological agents. 24 Combined, our data suggest that there is an overall impairment of endothelial cell culture in response to albumin exposed to glucose for longer durations.…”
Section: Metabolic Activitymentioning
confidence: 62%
“…These findings are in agreement with previous work that has shown that the metabolic activity of endothelial cells within a diabetic vasculature is reduced and that this can be reversed through the application of pharmacological agents. 24 Combined, our data suggest that there is an overall impairment of endothelial cell culture in response to albumin exposed to glucose for longer durations.…”
Section: Metabolic Activitymentioning
confidence: 62%
“…The underlying mechanisms responsible for the development of diabetes are a complex interplay of various and potential factors, such as increased thrombotic potential (29), endothelial dysfunction (19), and increased oxidative stress (1). In experimental studies, feeding a carbohydrate-enriched diet to normal or obese Zucker rats has been shown to induce insulin resistance and hyperinsulinemia, associated with an elevation in blood pressure (22), and development of vascular endothelial cell damages (35). It has also been shown that resveratrol improves vascular endothelial and postischemic cardiac function in various experimental models (11,23,27,34), which suggests that this agent may change the outcome of myocardial infarction in the diabetic state.…”
mentioning
confidence: 99%
“…[94] D-chiro-Inositol is able to prevent and reverse endothelial dysfunction in rat and rabbit blood vessels. [95] Some bone-related diseases are caused by excessive bone resorption by osteoclasts that are multinucleated giant cells formed by cell-cell fusion. D-chiro-Inositol has been shown to inhibit cell-cell fusion and the expression of several osteoclastogenic genes by downregulating nuclear factor of activated T cells c1.…”
Section: Biology and Medicinementioning
confidence: 99%